Toward a valid approach to nonprofit efficiency measurement - Coupet, Jason; Berrett, Jessica L. (Nonprofit management & leadership, 2019)
Past literature in nonprofit management uses the overhead ratio of nonprofits as a measure of efficiency. Although the overhead ratio might measure top‐heaviness, we argue that it does not measure nonprofit efficiency. To investigate this, we use financial and operational data to rank the efficiency of Habitat for Humanity affiliates with the overhead and administrative ratio, as well as data envelopment analysis (DEA) and stochastic frontier analysis (SFA), two of the most popular efficiency measures. While the DEA and SFA rankings are statistically correlated, overhead ratio rankings are negatively correlated with both SFA and DEA rankings. We argue that nonprofit scholars, managers, and donors should move away from concepts and measures of efficiency based on financial ratios, and toward ones that embrace maximizing what nonprofits are able to make and do.